Efficient photo catalysts based on silver doped ZnO nanorods for the photo degradation of methyl orange. Issue 17 (1st December 2019) - Bhatti, Muhammad Ali; Shah, Aqeel Ahmed; Almani, Khalida Faryal; Tahira, Aneela; Chalangar, Seyed Ebrahim; Chandio, Ali dad; Nur, Omer; Willander, Magnus; Ibupoto, Zafar Hussain
Abstract: In this study, the doped ZnO nanorods with silver (Ag) as photosensitive material are prepared by the solvothermal method. The structural and optical characterization is carried out by the scanning electron microscopy, X-ray diffraction, energy dispersive spectroscopy and UV–visible spectroscopy. The use of Ag as dopant did not alter the morphology of ZnO except sample 4 which has flower like morphology. The Ag, Zn and O are the main constituent of doped materials. The XRD revealed a hexagonal phase for ZnO and cubic phase for silver and confirmed the successful doping of Ag. The photocatalytic activity of Ag doped ZnO nanorods was investigated for the photo degradation of methyl orange. The photocatalytic measurements show that 88% degradation of methyl orange by the sample 4 within the 2 h of UV light treatment (365 nm) is significant advancement in the photocatalyst and provide the inexpensive and promising materials for the photochemical applications.